Elevated Red Cell Distribution Width Predicts the Adverse Outcome of Patients Hospitalized with Acute Exacerbation of Chronic Obstructive Pulmonary Disease (Chest & Heart Journal, 2023)
Background: Chronic obstructive pulmonary disease (COPD) is one of the leading causes of morbidity and mortality in the world. Acute exacerbation of chronic obstructive pulmonary disease (AECOPD) causes repeated hospitalization of patients. The readmission risk of these patients should be assessed by any means specially any laboratory test that would show consistent association. Red Blood Cell Distribution Width (RDW) is an automatically calculated measure of routine hemogram test which is very simple and inexpensive. Increased RDW is associated with prognosis of many medical conditions, but still not well evaluated for the prognosis of AECOPD.Objectives: To evaluate the RDW level for prediction of prognosis in patients hospitalized with AECOPD.Methods: A population-based observational cohort study conducted on patients who were hospitalized due to AECOPD in Shaheed Tajuddin Ahmad Medical College Hospital, Gazipur from January 2017 to December 2018. Clinical and laboratory test reports of all participants were recorded. They were observed to measure the incidence of readmission due to AECOPD, readmission from any other cause and composite end point of readmission or death during 60 days after discharge from hospital.Results: Total 146 patients were included in the study. Overall readmission rate of patients within 60 days of index hospitalization was 28.21%, among them 48.63% readmitted patients were due to AECOPD. Composite end point (readmission or death) were found significant (p